Interval decline in hemoglobin A is associated with annual clinical event rate in sickle cell anemia patients receiving maintenance apheresis RBC exchange. Issue 8 (3rd June 2019) - Kamyszek, Reed W.; Raval, Jay S.; Srinivasan, Amudan J.; Ansari, Andrea K.; Evans, Brooke A.; Rollins‐Raval, Marian A.; Poisson, Jessica L.; Shah, Nirmish R.; Welsby, Ian J.
Abstract : BACKGROUND: Apheresis red blood cell (RBC) exchange (RCE) is a standard intervention for patients with sickle cell anemia (SCA) who have had previous thromboembolic stroke or intractable chronic pain. Replacing sickling cells with those containing hemoglobin A (HbA) minimizes microvascular pathophysiology that produces clinical crises. Limited data exist regarding the interval changes in HbA between transfusions. We sought to describe the HbA decrement between RCE procedures and its relationship to clinical status. STUDY DESIGN AND METHODS: SCA patients (all hemoglobin SS disease) treated with maintenance RCE (n = 21) over a 15‐month period at two neighboring institutions were retrospectively reviewed. Time‐normalized daily HbA decrement was calculated to reflect loss of transfused RBCs, and annual events of either emergency department or hospital admissions for SCA complications were noted. Associations between HbA decrement and laboratory measures were calculated using mixed linear regression models and unpaired t test was used to compare HbA decrement between high and low event rate groups. RESULTS: A total of 31 events were recorded, and mean HbA decrement per day was 0.77 ± 0.16%. The mean interval between RCEs was 36 ± 12 days. Patients with more annual events exhibited a significantly greater daily HbA decrement (p = 0.007). No significant association between RBC unit age and HbA decrement or annual event rate was observed. CONCLUSIONS: Patients exhibiting greater daily HbA decrement were more likely to have multiple emergency department visits or admissions for sickling crises. Modulating HbA decrement may merit study as an intermediate metric for interventions to improve outcomes in hemoglobin SS disease. Abstract : See article on page 2493–2495, in this issue